Argument teoriomodelowy trzydzieści lat później - Czerniawski, Krzysztof (Filozofia Nauki, 2010)
The paper aims at describing the discussion about the model-theorethic argument of Hilary Putnam in the past thirty years. First of all it presents the view of Timothy Bays, who through scrupulous examination of the formal side of the argument demonstrates that in fact it has very little in common with the model-theory. It is rather a simple and purely philosophical argument, which isn't more reliable and conclusive than any other argument in philosophy. Putnam tries to block the answer of followers of the causal theory of reference by insisting that it is "just more theory", which could be erased by argument like any other language structure. In response meta-physical realists, like David Lewis and James Van Cleve, claim that "it is not causal language that fixes reference; it is causation itself". David Leech Anderson agrees with metaphysical realists that in principle causal theory could fix the reference, but in his opinion we do not have reliable and substantive theory of that kind, and it doesn't even seem probable that we will have such a theory in future. In conclusion, I agree with Putnam that the metaphysical realist says that "we-know-not-what fixes the reference relation we-know-not-how", and he doesn't have any chance of avoiding the demolition by the model-theorethic argument, because he still tries to separate sharply the realms of language and reality.